Topical Formulation of Herbal Nanocosmetics for Anti-Aging - Husni, Patihul; Eryani, Mikhania Christiningtyas (Universitas Padjadjaran (Unpad), 2024)
Skin aging is a biological process that involves a decline in skin function. Regarding prevention and inhibition of skin aging, use of cosmetic products is an option to avoid skin aging because it can improve texture and function of skin. Recently, development of a topical formulation of herbal nanocosmetics for anti-aging has grown increasingly popular. This review is aimed to summarize and describe topical formulation of herbal nanocosmetics for anti-aging application. In addition, this review also shows several studies performed by researchers in development of topical formulation of herbal nanocosmetics for anti-aging. The data were collected from published journals in the range of 2011-2023. Study result showed that nanoemulsion, nanostructured lipid carriers (NLC), solid lipid nanoparticles (SLN), niosomes, liposomes, ethosomes, and transfersomes are nanotechnology methods used to prepare herbal nanocosmetics for anti-aging in the cream or gel dosage form. In conclusion, herbal nanocosmetics combine the benefits of herbal extracts with nanotechnology which can be used to enhance the effectiveness of natural ingredients for anti-aging effect. Keywords: topical, herbal, nanocosmetics, anti-aging